The Impact of Return-to-Field and Targeted Trap-Neuter-Return on Feline Intake and Euthanasia at a Municipal Animal Shelter in Jefferson County, Kentucky - Daniel D. Spehar; Peter J. Wolf (Animals, 2020)
The number of cats and dogs impounded and euthanized at animal shelters in the USA has declined dramatically in recent decades. The Humane Society of the United States reported that in 1973 an estimated 13.5 million cats and dogs were euthanized nationwide; according to Best Friends Animal Society, in 2018 that number had been reduced to approximately 733,000. A disproportionate number of animals euthanized at shelters today are free-roaming feral and stray cats, who most often face euthanasia due to their temperament or a lack of shelter space. Over the past decade, two new management tactics—return-to-field (RTF) and targeted trap-neuter-return (TNR)—have exhibited the capacity to contribute to significant reductions in feline euthanasia and intake. The present study examines changes in feline euthanasia and intake, as well as impacts on additional metrics, at a municipal animal shelter in Jefferson County, KY, USA, after an RTF program was added to an ongoing community-based TNR program. A combined total of 24,697 cats were trapped, sterilized, vaccinated, and returned over 8 years as part of the concurrent RTF and TNR programs. Feline euthanasia at Louisville Metro Animal Services (LMAS) declined by 94.1% and feline intake dropped by 42.8%; the live-release rate (LRR) increased by 147.6% due primarily to reductions in both intake and euthanasia. The results of the present study corroborate prior research on the effectiveness of combining RTF and TNR and exemplify the flexibility available to communities in configuring such programs to align with their particular needs and resources.